Self-employment among in-movers and stayers in rural areas: Insights from Swedish register and survey data - Lina Aldén; Mats Hammarstedt; Per Skedinger (Research Institute of Industrial Economics (IFN), 2024)
Our use of longitudinal register data combined with a unique survey allows us to offer a more comprehensive picture of rural self-employment than in previous studies. We find that selfemployed in rural settings are more likely than those in metropolitan regions to employ others, but self-employment rates in rural areas are lower. There is substantial heterogeneity among the rural self-employed; in-movers are quite different from stayers in terms of their perceptions of the conditions necessary for business success and their employment practices. Policy initiatives aimed at fostering development in rural areas should consider these distinctions.
Keywords: J24; J61; R11; 330; Self-Employment; Labor Mobility; Regional Development; Rural Economics